The role of MEK inhibition in pediatric low-grade gliomas - Sheikh, Shehryar R.; Klesse, Laura J.; Mangum, Ross; Bui, Ashley; Siegel, Benjamin I.; Abdelbaki, Mohamed S.; Patel, Neha J. (Frontiers in Oncology, 2024)
Pediatric low-grade gliomas (pLGGs) are the most common brain tumors in children. Many patients with unresectable tumors experience recurrence or long-term sequelae from standard chemotherapeutics. This mini-review explores the emerging role of MEK inhibitors in the management of pLGGs, highlighting their potential to transform current treatment paradigms. We review the molecular basis for therapeutic MEK inhibition in the context of pLGG, provide an evidence base for the use of the major MEK inhibitors currently available in the market for pLGG, and review the challenges in the use of MEKi inhibitors in this population.